Morphology Characterization of Rhopalocera in Two Areas of Resort Bukit Tiga Puluh National Park Riau Province - Chahyadi, Ennie; Isda, Mayta Novaliza; Destiyana, Appriliya; Fitmawati, Fitmawati; Salbiah, Desita (Jurnal Biodjati, 2020)
Bukit Tiga Puluh National park (TNBT) of Riau Province is a nature conservation area with a high diversity of fauna, one of which is the butterfly. Butterfly species diversity is influenced by the vegetation in their habitat. The TNBT utilization zone has a habitat type with varied vegetation. There is no information about the species of butterflies in the area. This study aimed toÂ identify morphological characterÂ of butterflies and vegetation based on morphological characters. The method used was exploration. The catching area of the butterfly was the Granite waterfall and the Bukit Lancang path of TNBT utilization zone. Samples made as insectarium and herbarium. The Â identification of butterfly characters consisted of the head, thorax, abdomen, legs and wings. There were a number of different types of butterflies and plants between the Granite waterfall area (22 and 28 species) and the Bukit Lancang paths (5 and 9 species). The type of butterfly was dominated by the family Nymphalidae.Â This is due to the amount of vegetation and environmental conditions that are more favorable in the granite waterfall area. The key determinants of butterfly species are the characters of the wing. The results of this study can contribute to maintaining the TNBT butterflies in Riau Province and alsoÂ as database information of butterflies speciesÂ in Indonesia.